Effects of Cinnamon Spice on Postprandial Plasma Levels of Glucose and Insulin in Healthy Participant with Normal Weight (FS15-04-19). (13th June 2019) - Ezzat-Zadeh, Zahra; Henning, Susanne; Woo, Shih Lung; Yang, Jieping; Zhang, Lijun; Huang, Jianjun; Lee, Rupo; Thames, Gail; Heber, David; Li, Zhaoping
Abstract: Objectives: The objective of this study is to investigate the effect of one time intake of cinnamon spice on the postprandial glucose tolerance and insulin secretion following consumption of a high glycemic index meal in normal weight and glucose tolerance individuals. Methods: Sixteen healthy controls (BMI = 18.5–24.9 kg/m 2 and fasting blood glucose (BG) < 100 mg/dL) aging 20–50 years, who typically consume a low fiber/polyphenol diet (beige diet) were recruited for this study. Recruitment of overweight/obese, prediabetic participants is not completed (no data presented). Participants consume a typical American breakfast containing 50 g of carbohydrates (1/3 cup of oatmeal and 1 cup 2% milk) with or without cinnamon (6 g) followed by 1-week washout and crossover to the opposite intervention. The blood samples were taken at fasting state and at 30, 60, 90, 120, 150 and 180 minutes after the meal. The main outcome measures included BG and insulin. The secondary outcome measures were C-peptide and glucagon. Cinnamon spice (Indonesia) was purchased at the local grocery store (McCormick®) and contains 3.9% proanthocyanin. The statistical significance was set at P < 0.05 using SPSS. Results: Consumingcinnamon spice with the oatmeal significantly decreased the rate of glucose change from fasting state at 60 and 90 minutes after the meal by 37% and 31%, respectively. The peak postprandial BG and the areas under the curve (AUC) of glucose were also lowered by cinnamon compared to oatmeal alone but did not reach the significant levels. There was a trend towards significant decrease (21%, P = 0.08) in plasma insulin concentrations and a significant decrease in plasma C-peptide levels 30 minutes after ingestion of the meal with cinnamon. Cinnamon ingestion compared to oatmeal alone also significantly decreased plasma glucagon levels at 90 minutes after the meal test. Conclusions: Our results suggest that one time intake of cinnamon spice lowers the mean rate of glucose change following a high glycemic index meal in healthy individuals. Cinnamon also decreased plasma levels of insulin, C-peptide, and glucagon. Funding Sources: UCLA Center for Human Nutrition.